Sustaining Korea's Convergence to the Highest-Income Countries - Jones, Randall S.. (OECD Economics Department Working Papers, 2012)
While Korea remains one of the fastest-growing OECD economies, its potential growth rate per capita is projected to decelerate from around 4% during the current decade to around 2¼ per cent during the 2030s. Sustaining growth requires policies to mitigate the impact of rapid population ageing by increasing labour inputs from under-utilised segments of the population. In particular, female labour participation should be encouraged by better work-life balance and increasing the availability of high-quality, affordable childcare, in part by raising tuition fee subsidies and improving the quality of private childcare centres. More flexible employment and wage systems would increase the age at which older workers leave firms. For young people, improved vocational education at the secondary and tertiary levels would help overcome the labour mismatch problem and the overemphasis on tertiary education. Enhancing educational quality at all levels would promote productivity gains, including in services. Strengthened competition is also a key to narrow the large productivity gap between services and manufacturing